2021
DOI: 10.1093/bjsopen/zrab014
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in quality of life among Sri Lankan patients with haemorrhoids after invasive treatment: a longitudinal observational study

Abstract: Background Haemorrhoids is a common chronic disease that can significantly impact patients’ quality of life. Yet, few studies have evaluated health-related quality of life (HRQoL) of patients with haemorrhoids before and after treatment. This study investigated the HRQoL of patients with haemorrhoids before and after treatment and the change in HRQoL from baseline. Methods A prospective observational study of patients with haemorrhoids was conducted at two public hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…A simple translation of the questionnaire without any modification for cultural and linguistic context can result in an inaccurate measurement. According to our results the farsi translated HDSS and HSS questionaaires show both reliability and accuracy 7,10,18,26 …”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…A simple translation of the questionnaire without any modification for cultural and linguistic context can result in an inaccurate measurement. According to our results the farsi translated HDSS and HSS questionaaires show both reliability and accuracy 7,10,18,26 …”
Section: Discussionsupporting
confidence: 51%
“…According to our results the farsi translated HDSS and HSS questionaaires show both reliability and accuracy. 7,10,18,26 In a recent study, the COSMIN criterion was used to evaluate the methodological quality of both HDSS and HSS, which concluded that both tests exhibit acceptable qualities for evaluation and scoring. Future research in this field should include additional tests and evaluations utilizing both COSMIN criteria and a gold standard criterion for hemorrhoidal disease, with both English and Farsi versions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a longitudinal observational study, bleeding and soiling showed significant improvements in symptom severity from weeks 4 to 8 post-surgery, whereas pain, itching, and swelling/prolapse did not[ 15 ]. This difference in the improvement of specific symptoms may be attributed to the surgical techniques used.…”
Section: Discussionmentioning
confidence: 99%